1998
DOI: 10.1021/bi9721290
|View full text |Cite
|
Sign up to set email alerts
|

A Designed Cavity in the Hydrophobic Core of a Four-α-Helix Bundle Improves Volatile Anesthetic Binding Affinity

Abstract: The structural features of protein binding sites for volatile anesthetics are being explored using a defined model system consisting of a four-alpha-helix bundle scaffold with a hydrophobic core. Earlier work has demonstrated that a prototype hydrophobic core is capable of binding the volatile anesthetic halothane. Exploratory work on the design of an improved affinity anesthetic binding site is presented, based upon the introduction of a simple cavity into a prototype (alpha 2)2 four-alpha-helix bundle by rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
101
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(110 citation statements)
references
References 51 publications
9
101
0
Order By: Relevance
“…The cysteine-specific spin label (1-oxyl-2,2,5,5-tetramethylpyrroline-3-methyl)methanethiosulfonate (MTSSL) was purchased from Toronto Research Chemicals (Toronto, Canada). MTSSL was attached to the modified LD2 peptides as described earlier (26). In brief, 1.1 mM LD2 peptide and a 10-fold excess of MTSSL were mixed and stirred for 12 h in a 4:1 (vol/vol) solution of 130 mM NaCl, 20 mM sodium phosphate buffer (pH 7.2), and acetonitrile.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cysteine-specific spin label (1-oxyl-2,2,5,5-tetramethylpyrroline-3-methyl)methanethiosulfonate (MTSSL) was purchased from Toronto Research Chemicals (Toronto, Canada). MTSSL was attached to the modified LD2 peptides as described earlier (26). In brief, 1.1 mM LD2 peptide and a 10-fold excess of MTSSL were mixed and stirred for 12 h in a 4:1 (vol/vol) solution of 130 mM NaCl, 20 mM sodium phosphate buffer (pH 7.2), and acetonitrile.…”
Section: Methodsmentioning
confidence: 99%
“…Paramagnetic relaxation caused by sitedirected spin labeling can be employed as a powerful tool for determining the solution structure of a molecule because the paramagnetic center can enhance the spin lattice relaxation of magnetic nuclei in a distance-dependent manner (3,13). Oxidized nitroxide has been commonly used as such a paramagnetic center, and previous reports showed that spin labeling can be achieved by the MTSSL method, which covalently links nitroxide to a solvent-exposed cysteine residue through methanethiosulfonate (26). Using a similar method, we performed site-directed labeling of the LD2 peptide.…”
Section: Structure Of the Fat Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…All fits showed an R 2 value Ͼ 0.99. core in these GPCRs. Furthermore, with the use of designed four-␣-helical bundles (Johansson et al, 1998(Johansson et al, , 2000, and other soluble proteins with hydrophobic cavities Eriksson et al, 1992), it has been shown that preformed accessible cavities are important features to facilitate anesthetic binding. Although inhaled anesthetics have divergent chemical structures, the molecules are relatively small (90 -160 Å 3 ) and have few interactive atoms or groups to provide much selectivity, compared with other molecules that interact with GPCRs, such as biogenic amines and retinal.…”
Section: Table 1 Effects Of Halothane On Retinal Binding Kineticsmentioning
confidence: 99%
“…Such a designed fourhelix bundle protein, (␣ 2 ) 2 , has recently been described and used as a template for anesthetic binding studies (8).…”
mentioning
confidence: 99%